Improving hip fracture outcomes using routinely collected health data - Metcalfe, D (2019)
Hip fracture is associated with high morbidity and mortality but outcomes can be improved through dedicated clinical pathways that deliver evidence-based multidisciplinary care. The National Hip Fracture Database (NHFD) is a national clinical audit that exists to improve hip fracture care by providing hospital-level performance data through online dashboards and an annual report. The aim of this thesis was to explore how national clinical audit can improve hip fracture care and outcomes. In Chapter 2, a systematic review found little existing evidence to show that releasing performance data into the public domain can change healthcare decisions, clinical performance, or patient outcomes. Importantly, the evidence could not exclude an effect and it seems likely that data will continue to be released to the public in efforts to improve performance. Chapter 3 shows that specific identification of performance outliers is relatively insensitive to the model used for risk-adjustment and may not be enhanced by routine linkage of the NHFD to other datasets. In Chapter 4, an interrupted time series and difference-in-differences study did not find any evidence that introduction of the NHFD alone improved performance measures or patient outcomes. However, integration of the NHFD with the Hip Fracture Best Practice Tariff (BPT) - which pays hospitals a supplement for meeting evidence-based care standards - was associated with marked and sustained improvements across both performance measures and patient outcomes. This suggests that an integrated system for rewarding best practice can improve outcomes beyond that of a voluntary audit of national clinical standards. The BPT rewards hospitals for meeting seven care standards. In Chapter 5, an observational study using NHFD data found substantial deviation from national guidance around provision of total hip arthroplasty (THA), which is not yet a BPT standard. Under-provision of THA appears to disproportionately affect patients living in deprived areas and those presenting to hospital at weekends. One possible reason for under-provision of THA is that the evidence is uncertain. There is concern that randomised trials may overstate the advantages of THA when used in routine clinical practice. However, Chapter 6 combined meta-analysis of trial data with a propensity score matched cohort study using the NHFD and did not find evidence that outcomes were worse outside clinical trials. Importantly, both studies reported an association between THA and reduced 12-month mortality, which clearly requires urgent further investigation. This thesis shows that the NHFD is a valuable resource both for auditing standards of care and embedding studies aimed at learning from the outcomes of patients with hip fractures. If the findings in Chapter 6 are supported by further work, the provision of THA to eligible patients should be considered as a future quality standard that must be met for payment of the BPT.